If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-15=-6x+3x-9
We move all terms to the left:
-15-(-6x+3x-9)=0
We add all the numbers together, and all the variables
-(-3x-9)-15=0
We get rid of parentheses
3x+9-15=0
We add all the numbers together, and all the variables
3x-6=0
We move all terms containing x to the left, all other terms to the right
3x=6
x=6/3
x=2
| -3=-20x+16 | | 7/4=x/15 | | -18x+14=-7 | | 7x-6=76 | | 10x-4(7-11x)=-190 | | 35+3x=45+2× | | 10/x=30/24 | | 77=5x-18 | | 100-3(2x-6)=10 | | 4(4j-5)=11j+10 | | 3+3/2x+4=4x+-5/2x | | x/12=80/120 | | 3(1-9a)=22a=2(2a-9)-15 | | Y=0.30x+.731 | | (x+7)^(3)=1000 | | 4w^2+5w+10=0 | | 3n=5n-40 | | Y=0.30*x+.731 | | 1/2-1/8q=(q-1)÷4 | | 3n=5n=40 | | -2x+8=+4 | | -27-3x=-6x-(-8x-3) | | 1/4x-13=4 | | 8s—(8+6s)=20 | | X(x+8)=27 | | 19a+-17a+-15a=-13 | | 25x+55=30x-10 | | 0.4x+0.9(10-x)=5 | | 25x+55=36x-10 | | 25x=55=30x-10 | | Y-4=8+x | | -1-(k+4)=35+4k |